Sustainable Peacebuilding and Social Justice in Times of Transition Findings on the Role of Education in Myanmar - Lopes Cardozo, Mieke T.A.; Maber, Elizabeth J.T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book offers a unique insight into the ways in which education systems, governance, and actors at multiple scales interact in initial steps towards building peace. It presents a spectrum of recently conducted research in the context of Myanmar, a society in the midst of challenging transitions, politically, socio-culturally and economically. Divided in 3 thematical research areas, the first part on Myanmar's policy landscape aims to unravel the integration of peacebuilding into the education sector at macro and micro policy levels. The second part examines the role teachers play in processes of peacebuilding, and the third part examines ways in which formal and non-formal peacebuilding education programs address the agency of youth in Myanmar. This book is an essential guide for students embarking in the field of education, conflict and peacebuilding.
Foreword (Mario Novelli and Alan Smith) -- Chapter 1. Introduction (Mieke Lopes Cardozo and Elizabeth Maber) -- Chapter 2. Analytical framework, Methodology and key definitions (Mieke Lopes Cardozo) -- PART 1. Myanmar's Policy Landscape -- Chapter 3. Contemporary conflict-affected & peacebuilding context of Myanmar (Elizabeth Maber) -- Chapter 4. Education and policy challenges of a situation in flux (Ritesh Shah, Khin Mar Aung and Mieke Lopes Cardozo) -- Chapter 5. Policy implications for language of instruction (Aye Aye Nyein, Ritesh Shah and Khin Mar Aung) -- PART 2. Teachers and Peacebuilding -- Chapter 6. Teachers' roles in ongoing processes of peacebuilding and conflict (Elizabeth Maber, Sean Higgins and Hla Win May Oo) -- Chapter 7. Teacher education and curriculum reform (Sean Higgins) -- Chapter 8. Non-State teaching in Mon (Katharina Buske and Taru Niskanen) -- PART 3 - Youth and Peacebuilding -- Chapter 9. Youth's restricted space for peacebuilding in and beyond education (Mieke Lopes Cardozo and Sean Higgins) -- Chapter 10. Youth in formal and non-formal education (Elizabeth Maber, Naw Naw Paul, Aye Aye Nyein, and Sean Higgins) -- Chapter 11. Youth experiences of education for peacebuilding (Tabea Cambell Pauli and Kyimet Schipper) -- Chapter 12. Concluding reflections and possible ways forward (Mieke Lopes Cardozo and Elizabeth Maber).-.
Keywords: Human rights; Economic development; International education .; Comparative education; Sociology -- Methodology; Human Rights; Development Studies; International and Comparative Education; Sociological Methods